2014
DOI: 10.1021/ol503252t
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Synthesis of Six-Membered Benzofuzed Phosphacycles via Carbon–Phosphorus Bond Cleavage

Abstract: The palladium-catalyzed synthesis of dibenzofused six-membered phosphacycles via carbon-phosphorus bond cleavage is developed. This method is compatible with a range of functional groups, such as esters, amides, and carbamates, which is in sharp contrast to the limitations of the classical method using organolithium reagents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 50 publications
1
37
0
Order By: Relevance
“…Chatani and co‐workers further developed an intramolecular quaternization of a phosphino group with an aryl bromide to give six‐membered phosphonium salt 45 , which was transformed into 46 via C−P cleavage (Scheme ) . The mechanism of C−P bond activation is similar to that of the previously discussed reaction, but a reducing reagent, (Me 3 Si) 3 SiH, was needed to covert palladium(II) into an active palladium(0) species.…”
Section: Phosphination With the Cleaved P‐moietymentioning
confidence: 90%
“…Chatani and co‐workers further developed an intramolecular quaternization of a phosphino group with an aryl bromide to give six‐membered phosphonium salt 45 , which was transformed into 46 via C−P cleavage (Scheme ) . The mechanism of C−P bond activation is similar to that of the previously discussed reaction, but a reducing reagent, (Me 3 Si) 3 SiH, was needed to covert palladium(II) into an active palladium(0) species.…”
Section: Phosphination With the Cleaved P‐moietymentioning
confidence: 90%
“…Inspired by the strategy used in the synthetic method to access mono-aryl substituted phosphines, Chatani and coworkers modified and adapted this reaction to produce dibenzofused six and fivemembered phosphacycles (Scheme 50). This is a class of phospholes which has rapidly found applications in material science due to their unique optical and electronic properties [124][125]. Conventional synthetic methods using highly reactive ragents for their preparation have been limited by low functional group compatibility.…”
Section: Scheme 49mentioning
confidence: 99%
“…The authors highlighted the compatibility of their method with several functional groups including esters, amides, and carbamates. However they indicated that the extension of this method to the synthesis of seven-membered phosphacycles was unsuccessful [125].…”
Section: Scheme 49mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the same group reported the syntheses of substituted phenoxaphosphines and phenophosphazine derivatives via intramolecular aryl exchange catalysed by Pd (Scheme 1.65). [228] Scheme 1.65 Synthesis of 6-membered benzofused phosphacycles via Pd-catalysed intramolecular aryl exchange.…”
Section: Scheme 164 Synthesis Of Annulated Phosphole Derivatives Viamentioning
confidence: 99%